The New Civil Procedure Code And The Binding Precedents: Reflections In Search Of An Adequate Application - Sartori, Ellen Carina Mattias (2016)
The new Civil Procedure Code revered the binding precedents as a way of shield the constitutionals principles of isonomy and legal security, as well as jurisdiction unit. The absence of a juridical culture based on precedents in Brazil, however, brings out several imprecisions that put on threat the objectives of the new Code. The article, thus, reflects about some application and flexibility precedent´s techniques, developed over the years in the countries that adopted the common law, that would be essential for the new code to reach the intention to establish a fast, effective, fair and equal jurisdictional activity.